Effects of Ricinus communis oil esters on salivary glands of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) - Arnosti, Andre [UNESP]; Brienza, Paula Desjardins [UNESP]; Scopinho Furquim, Karim Christina [UNESP]; Chierice, Gilberto Orivaldo; Claro Neto, Salvador; Bechara, Gervasio Henrique [UNESP]; Sampieri, Bruno Rodrigues [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
This study showed the interference of esters extracted from Ricinus communis in the secretory cycle of salivary glands of Rhipicephalus sanguineus ticks, which consequently caused collateral effects on their feeding process. Ticks attached on hosts which were fed with commercial feed containing different concentrations of R. communis oil esters suffered damages such as cytoplasmic changes in their salivary glands, notably in the acinar cells, impairing the functioning of the acini and accelerating the organs degeneration as a whole. It was found that esters interfered with the activity of cellular secretion by changing the glycoprotein of salivar composition especially in acini II cells. It was also shown that the damages caused by esters in the salivary glands cells of these ectoparasites increased in higher concentrations of the product and degenerative glandular changes were more pronounced. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ricinus communis; Rhipicephalus sanguineus; Salivary gland; Esters; Glandular secretion; Tick control